Two‐step crystal–crystal phase transformation of N‐salicylidene‐p‐aminobenzoic acid by gas–solid reaction with aqua–ammonia vapour. Issue 1 (27th January 2021) - Sugiyama, Haruki; Uekusa, Hidehiro
Abstract : N ‐Salicylidene‐ p ‐aminobenzoic acid crystals undergo a two‐step gas–solid reaction with aqua–ammonia vapour in the crystalline state. Moreover, the photochromic behaviour of the crystals was switched from OFF to ON and back to OFF through a phase transformation. Abstract : Crystal–crystal phase transformation by external stimuli has attracted significant attention for application in switchable materials, which can change their structures and properties. Herein, it is revealed that N ‐salicylidene‐ p ‐aminobenzoic acid crystals undergo a two‐step crystal–crystal phase transformation through a gas–solid reaction with aqua–ammonia vapour. The photochromic behaviour of the crystals switched from nonphotochromic to photochromic and back to nonphotochromic via a phase transformation. The two‐step phase transformation and photochromic behaviour change were characterized and correlated by X‐ray crystal structure analysis, UV–Vis spectroscopy, differential scanning calorimetry and scanning electron microscopy. This article is the first report to capture the stepwise structural change in the gas–solid (acid–base) reaction of ammonia with benzoic acid derivatives.